Surface Treatment Powder
A surface-treated powder using modified silicone and cation-releasing substances forms a soft cosmetic film, effectively preventing makeup transfer to masks by altering film formation methods, addressing the hardness and transfer issues of conventional films.
Patent Information
- Application Number
- JP2023521013
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-14
- Filing Date
- 2022-05-09
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2042-05-09
AI Technical Summary
Conventional cosmetic films formed by cosmetic film-forming agents result in a hard and unpleasant texture, and they fail to effectively prevent makeup transfer to masks.
A surface-treated powder composed of a modified silicone with a carboxyl group, a substance releasing divalent or higher cations, and a carboxyl or sulfonic acid group-forming polymer, which forms a cosmetic film through interactions between powders rather than film-forming agents, enhancing softness and reducing makeup transfer.
The solution results in a soft-touch cosmetic film that significantly reduces makeup transfer to masks, providing a superior user experience and improved film formation.
Smart Images

Figure 0007610702000001 
Figure 0007610702000002 
Figure 0007610702000003
Abstract
Description
[Technical field]
[0001] The present invention generally relates to a surface-treated powder obtained by surface-treating a base powder, and particularly to a surface-treated powder used in cosmetics. [Background technology]
[0002] 2. Description of the Related Art Conventionally, in order to prevent makeup from coming off, cosmetics have been proposed that aim to increase the water resistance and sebum resistance of the cosmetic film obtained by applying the cosmetic.
[0003] In addition, with increased awareness of hygiene in recent years and more opportunities to wear masks, there is a desire to reduce the transfer of makeup to masks.
[0004] For example, International Publication WO2020 / 036064 (Patent Document 1) describes an oil-in-water emulsion cosmetic that contains (A) a carboxylic acid-modified silicone that is liquid at 50°C, (B) a vinyl polymer emulsion, (C) a basic compound, and (D) an inorganic UV protection agent consisting of a hydrophobic fine metal oxide particle, for the purpose of providing an oil-in-water emulsion cosmetic that has a high SPF value, minimizes the loss of the feel and sensation of use that are unique to oil-in-water emulsion cosmetics, and has excellent properties such as water resistance of the film (cosmetic film).
[0005] Furthermore, International Publication No. WO2009 / 022621 (Patent Document 2) describes a surface-treated powder obtained by treating the powder surface with an organopolysiloxane derivative having a specific structure containing a carboxyl group, which is used as a surface treatment agent, for the purpose of improving the water resistance, sebum resistance, and feel when used of the surface-treated powder to be blended into a cosmetic composition, and a cosmetic composition containing the surface-treated powder. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. WO2020 / 036064 [Patent Document 2] International Publication No. WO2009 / 022621 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the cosmetics described in Patent Documents 1 and 2, the cosmetic film-forming agents contained in the cosmetics to enhance water resistance and sebum resistance combine with each other to form a hard film, which can result in an unpleasant, crispy feeling after drying.
[0008] Therefore, an object of the present invention is to provide a surface-treated powder for incorporation into cosmetics that is capable of forming a cosmetic film that feels soft to the touch and that can prevent makeup from transferring onto a mask to an equal or greater extent than conventional methods. [Means for solving the problem]
[0009] As a result of intensive research, the present inventors have found that a cosmetic film with a soft feel can be formed by forming a cosmetic film not between cosmetic film-forming agents but by interaction between powders via cations. Based on this finding, the present invention is configured as follows.
[0010] The surface-treated powder according to the present invention is a base powder that has been surface-treated with (A) a modified silicone having a carboxyl group, (B) a substance capable of releasing divalent or higher cations, and (C) a polymer having a carboxyl group or a sulfonic acid group.
[0011] In this way, it is possible to provide a surface-treated powder for incorporation into cosmetics that can form a cosmetic film that feels soft to the touch and that can prevent makeup from transferring onto a mask to an equal or greater extent than conventional methods.
[0012] In the surface-treated powder according to the present invention, the base powder is preferably one or more selected from the group consisting of talc, titanium oxide, silica, mica, iron oxide, and zinc oxide.
[0013] In the surface-treated powder according to the present invention, (B) the substance capable of releasing divalent or higher cations is preferably one or more oxides, hydroxides, or salts selected from the group consisting of calcium, magnesium, iron, aluminum, and zinc.
[0014] The cosmetic according to the present invention contains 10 parts by mass or more of any of the above surface-treated powders.
[0015] A cosmetic method according to the present invention includes applying a cosmetic containing any one of the above-mentioned surface-treated powders to the skin to form a cosmetic film, and then adhering moisture to the cosmetic film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The surface-treated powder, cosmetic, and cosmetic method of the present invention will be described in detail below with specific examples. Note that the present invention is not limited to the embodiments shown below, and various modifications are possible within the scope of the technical concept of the present invention.
[0017] The surface-treated powder according to the present invention is a base powder that has been surface-treated with (A) a modified silicone having a carboxyl group, (B) a substance capable of releasing divalent or higher cations, and (C) a polymer having a carboxyl group or a sulfonic acid group.
[0018] <Base material powder> The inorganic material used as the base powder is not particularly limited, and for example, one or more selected from the group consisting of talc, titanium oxide, silica, mica, iron oxide, and zinc oxide can be used. Among these, talc or titanium oxide is particularly preferred. For example, a mixture of talc and pigment-grade titanium oxide can be used as the base powder.
[0019] The particle shape of the base powder may be any shape commonly used in cosmetics, such as spherical, approximately spherical, hemispherical, spindle-shaped, needle-shaped, plate-shaped, polyhedral, star-shaped, etc., and is preferably a rounded shape such as spherical, approximately spherical, hemispherical, etc. The particles of the base powder may be either non-porous or porous.
[0020] The base powder can be contained in the surface treatment powder in an amount of, for example, 70 parts by mass or more and 90 parts by mass or less, but is not limited thereto.
[0021] <(A) Modified silicone having a carboxyl group> The type of modified silicone having a carboxyl group is not particularly limited, and may be any silicone that is commonly used in cosmetics. For example, biscarboxydecyl dimethicone and / or carboxydecyl dimethicone can be used.
[0022] The amount of the modified silicone having a carboxyl group is not limited, and may be, for example, 1 part by mass or more and 5 parts by mass or less, and preferably 1.0 part by mass or more and 3.0 parts by mass or less, per 100 parts by mass of the surface-treated powder.
[0023] <(B) Substance capable of releasing divalent or higher cations> As the substance capable of releasing divalent or higher cations, it is preferable to use one or more oxides, hydroxides, or salts selected from the group consisting of calcium, magnesium, iron, aluminum, and zinc. Specifically, it is preferable to use, for example, calcium carbonate, calcium chloride, calcium hydroxide, and aluminum oxide.
[0024] The substance capable of releasing divalent or higher cations is not limited, and may be contained, for example, in an amount of 0.5 parts by mass or more and 3 parts by mass or less, and preferably 0.8 parts by mass or more and 2.6 parts by mass or less, per 100 parts by mass of the surface-treated powder.
[0025] <(C) Polymer Having Carboxyl or Sulfonic Acid Group> The polymer having a carboxyl group may be any polymer commonly used in cosmetics, such as carbomer, (acrylates / alkyl acrylate (C10-30)) crosspolymer, and xanthan gum.The polymer having a sulfonic acid group may be, for example, (hydroxyethyl acrylate / sodium acryloyldimethyl taurate) copolymer, (sodium acrylate / acryloyldimethyl taurate / dimethylacrylamide) crosspolymer.
[0026] The polymer having a carboxyl group or a sulfonic acid group may be contained, for example, in an amount of 5 parts by mass or more and 20 parts by mass or less, and preferably 5 parts by mass or more and 11 parts by mass or less, per 100 parts by mass of the surface-treated powder, without being limited thereto.
[0027] <Surface treatment method> The surface treatment method for obtaining the surface-treated powder of the present invention may be appropriately selected in consideration of the physical properties of the base powder and the surface treatment agent. For example, the method may be a method in which the base powder is dispersed in a dispersion medium, the surface treatment agent is added and stirred, and then the mixture is filtered and dried, or a method in which the surface treatment agent is added to a dry powder and mixed, but is not limited thereto.
[0028] <Cosmetics> When the surface-treated powder is blended in a cosmetic, other ingredients blended in a normal cosmetic may be added, such as moisturizers, (C) aqueous thickeners such as methylcellulose and guar gum as thickeners other than the polymer having a carboxyl group or a sulfonic acid group, gelling agents, preservatives, antibacterial agents, colorants, fragrances, salts, antioxidants, pH adjusters, chelating agents, cooling agents, anti-inflammatory agents, vitamins, amino acids, etc., and the added ingredients are not particularly limited.
[0029] When the surface-treated powder is blended in a cosmetic, the surface-treated powder is preferably contained in an amount of 10 parts by mass or more, and particularly preferably 20 parts by mass or more, per 100 parts by mass of the cosmetic.
[0030] <How to apply makeup> When applying makeup using the cosmetic of the present invention, a cosmetic containing the surface-treated powder is applied to the skin to form a cosmetic film, and then moisture is applied to the cosmetic film. For example, when the surface-treated powder of the present invention is blended into a powder foundation as a cosmetic, a normal powder foundation application method is used to form a cosmetic film on the skin. The method of applying moisture to the cosmetic film is not limited, but preferably, water at room temperature is sprayed to apply moisture uniformly to the entire cosmetic film. By applying moisture, the powder forms a film via cations, and mask transfer can be reduced. Preferably, after applying moisture, the product is dried at room temperature for 5 minutes before wearing a mask.
[0031] In this way, a cosmetic film that feels soft to the touch can be formed, and the transfer of makeup onto the mask can be prevented to an equal or greater extent than in the past. EXAMPLES
[0032] The composite surface-treated inorganic powder according to the present invention will be described in more detail below by showing specific production examples and test results.
[0033] <Example 1> 84.86 parts by mass of talc (THC-7P, manufactured by Hyogo Clay), 1.7 parts by mass of calcium carbonate, and 10.61 parts by mass of carbomer (Carbopol 934 polymer, manufactured by Lubrizol) were mixed and stirred in a mixer. 2.83 parts by mass of biscarboxydecyl dimethicone (SILSOFT INX, manufactured by Momentive Performance Materials) were added to the resulting mixture and mixed to obtain the surface-treated powder of Example 1.
[0034] <Example 2> The surface-treated powder of Example 2 was obtained in the same manner as in Example 1, except that the biscarboxydecyl dimethicone in Example 1 was changed to carboxydecyl dimethicone (manufactured by Dow Toray, DOWSIL ES-5800).
[0035] <Example 3> The surface-treated powder of Example 3 was obtained in the same manner as in Example 1, except that the 2.83 parts by mass of biscarboxydecyl dimethicone in Example 1 was changed to a mixture of 1 part by mass of biscarboxydecyl dimethicone (SILSOFT INX) and 1.83 parts by mass of carboxydecyl dimethicone (DOWSIL ES-5800).
[0036] <Example 4> The surface-treated powder of Example 4 was obtained in the same manner as Example 1, except that the talc in Example 1 was changed from 84.86 parts by mass to 77.30 parts by mass, the biscarboxydecyl dimethicone was changed from 2.83 parts by mass to 4.25 parts by mass, the calcium carbonate was changed from 1.7 parts by mass to 2.55 parts by mass, and the carbomer was changed from 10.61 parts by mass to 15.9 parts by mass.
[0037] <Example 5> The surface-treated powder of Example 5 was obtained in the same manner as Example 1, except that the talc in Example 1 was changed from 84.86 parts by mass to 88.65 parts by mass, the biscarboxydecyl dimethicone was changed from 2.83 parts by mass to 2.125 parts by mass, the calcium carbonate was changed from 1.7 parts by mass to 1.275 parts by mass, and the carbomer was changed from 10.61 parts by mass to 7.95 parts by mass.
[0038] <Example 6> The surface-treated powder of Example 6 was obtained in the same manner as Example 1, except that the talc in Example 1 was changed from 84.86 parts by mass to 92.425 parts by mass, the biscarboxydecyl dimethicone was changed from 2.83 parts by mass to 1.415 parts by mass, the calcium carbonate was changed from 1.7 parts by mass to 0.85 parts by mass, and the carbomer was changed from 10.61 parts by mass to 5.31 parts by mass.
[0039] <Example 7> The surface-treated powder of Example 7 was obtained in the same manner as in Example 1, except that the 1.7 parts by mass of calcium carbonate in Example 1 was changed to 1.7 parts by mass of aluminum oxide.
[0040] <Example 8> The surface-treated powder of Example 8 was obtained in the same manner as in Example 1, except that the talc in Example 1 was changed from 84.86 parts by mass to 84.68 parts by mass, and the calcium carbonate was changed from 1.7 parts by mass to 1.88 parts by mass of calcium chloride.
[0041] <Example 9> The surface-treated powder of Example 9 was obtained in the same manner as in Example 1, except that the talc in Example 1 was changed from 84.86 parts by mass to 84.25 parts by mass, and the calcium carbonate was changed from 1.7 parts by mass to 2.31 parts by mass of calcium hydroxide.
[0042] <Example 10> The surface-treated powder of Example 10 was obtained in the same manner as in Example 1, except that 10.61 parts by mass of the carbomer of Example 1 was changed to 10.61 parts by mass of (hydroxyethyl acrylate / Na acryloyldimethyl taurate) copolymer (manufactured by SEPPIC, SEPINOV EMT-10).
[0043] <Example 11> The surface-treated powder of Example 11 was obtained in the same manner as in Example 1, except that 10.61 parts by mass of the carbomer of Example 1 was changed to 10.61 parts by mass of (acrylates / alkyl acrylate (C10-C30)) crosspolymer (PEMULEN TR-1, manufactured by Lubrizol).
[0044] <Example 12> The surface-treated powder of Example 12 was obtained in the same manner as in Example 1, except that the 84.86 parts by mass of talc in Example 1 was changed to 84.86 parts by mass of pigment-grade titanium oxide (MP-25, manufactured by Teika).
[0045] <Example 13> The surface-treated powder of Example 13 was obtained in the same manner as Example 1, except that the 84.86 parts by mass of talc in Example 1 was changed to a total of 84.86 parts by mass of talc and pigment-grade titanium oxide (MP-25, manufactured by Teika) in a mass ratio of 6:4.
[0046] <Example 14> A surface-treated powder of Example 14 was obtained in the same manner as in Example 1, except that the 84.86 parts by mass of talc in Example 1 was changed to 84.86 parts by mass of red iron oxide.
[0047] <Example 15> A surface-treated powder of Example 15 was obtained in the same manner as in Example 1, except that the 84.86 parts by mass of talc in Example 1 was changed to 84.86 parts by mass of yellow iron oxide.
[0048] <Example 16> A surface-treated powder of Example 16 was obtained in the same manner as in Example 1, except that the 84.86 parts by mass of talc in Example 1 was changed to 84.86 parts by mass of black iron oxide.
[0049] <Example 17> A surface-treated powder of Example 17 was obtained in the same manner as in Example 1, except that the 84.86 parts by mass of talc in Example 1 was changed to 84.86 parts by mass of silica.
[0050] <Example 18> A surface-treated powder of Example 18 was obtained in the same manner as in Example 1, except that the 84.86 parts by mass of talc in Example 1 was changed to 84.86 parts by mass of zinc oxide.
[0051] <Comparative Example 1> 100 parts by mass of the talc used in Example 1 was used as the powder of Comparative Example 1.
[0052] <Comparative Example 2> A surface-treated powder of Comparative Example 2 was obtained in the same manner as in Example 1, except that the 2.83 parts by mass of biscarboxydecyl dimethicone in Example 1 was changed to 2.83 parts by mass of dimethicone.
[0053] <Comparative Example 3> 2L of water was placed in a beaker, and 200g of talc was added while stirring to form a slurry, and then sodium hydroxide was added to adjust the pH to 10. 2.4g of biscarboxydecyl dimethicone, 4.2g of carboxydecyl dimethicone, and 4.5g of calcium chloride were added thereto, and the mixture was aged for 30 minutes. The resulting dispersion was filtered, dried, and pulverized to obtain the surface-treated powder of Comparative Example 3.
[0054] <Comparative Example 4> A surface-treated powder of Comparative Example 4 was obtained in the same manner as in Example 1, except that the 84.86 parts by mass of talc in Example 1 was changed to 84.83 parts by mass, and the 1.73 parts by mass of calcium carbonate was changed to 1.73 parts by mass of sodium chloride.
[0055] <Comparative Example 5> 2.83 parts by mass of biscarboxydecyl dimethicone (SILSOFT INX) was added to 97.17 parts by mass of talc and mixed in a mixer to obtain a surface-treated powder of Comparative Example 5.
[0056] The mask transfer and mask abrasion of the powders obtained in each Example and Comparative Example were evaluated as follows. Since it was difficult to evaluate color transfer for the surface-treated powders of Examples 1 to 11 and Comparative Examples 1 to 5, which used only talc as the base powder, pigment-grade titanium oxide was mixed as a colorant at a mass ratio of surface-treated powder:pigment-grade titanium oxide of 6:4, and then evaluation was performed.
[0057] <Evaluation of transfer of surface treatment powder onto mask> 2mg / cm of powder in an area of 6cm x 3.5cm on artificial leather 2 The coating was applied to the black polyester fabric. Water was sprayed from a spray bottle about 15 cm away for about 2 seconds, and the fabric was dried at 60°C for 10 minutes. The amount of water sprayed was 1 g. A black polyester cloth was placed on the resulting coating, and then a glass plate was placed on top of that, and a 1 kg weight was placed on top of that, and the fabric was left for 10 seconds. A color difference meter was used to measure the lightness (L1) of the black polyester cloth that had come into contact with the coating, and the lightness (L2) of the black polyester cloth before coming into contact with the coating, and the value of L1 / L2 was calculated. The closer L1 / L2 is to 1, the more the color transfer is suppressed. The results are shown in Table 1.
[0058] <Evaluation of mask abrasion of surface treatment powder> 2mg / cm of powder in an area of 6cm x 3.5cm on artificial leather 2The coating was applied. Water was sprayed from a spray bottle about 15 cm away for about 2 seconds, and then dried at 60°C for 10 minutes. The amount of water sprayed was 1g. A black polyester cloth was fixed to a puff and placed on the coating film. A 1kg weight was placed on top of it, and the puff was slid for about 1 second. A color difference meter was used to measure the lightness (L3) of the black polyester cloth that had come into contact with the coating film and the lightness (L2) of the black polyester cloth before coming into contact with the coating film, and the value of L3 / L2 was calculated. It can be said that the closer L3 / L2 is to 1, the more color transfer is suppressed. The results are shown in Table 1.
[0059] [Table 1]
[0060] As shown in Table 1, in the surface-treated powders of Examples 1 to 18, mask transfer and mask rubbing were suppressed more than in Comparative Examples 1 to 5. In particular, in the case of mask rubbing, the L3 / L2 values were suppressed to less than 3.0 in all of Examples 1 to 18, but in all of Comparative Examples 1 to 5, the L3 / L2 values were 3.0 or more.
[0061] <Cosmetics> Powder cosmetics having the compositions shown in Table 2 below were prepared by conventional methods. In Table 2, the blending amount of each component is shown in parts by mass. The resulting cosmetics were evaluated for mask transfer and mask rubbing according to the following criteria. The results are shown in Table 2 together with the formulations.
[0062] The details of the raw materials in the table are as follows: Talc: Hyogo Clay THC-7P Pigment grade titanium dioxide: Teika MP-25 Red iron oxide: Titanium Industries R-516HP Yellow iron oxide: Titanium Industries LL-100HP Black iron oxide: Titanium Industries BL-100HP Mica: Japan Sericite JS-A Silica: Teika TMS-10 Diphenylsiloxyphenyl trimethicone: Shin-Etsu Chemical Co., Ltd. KF-56A Vaseline: Chloratum V made by Croda Japan Diisostearyl malate: Cosmol 222, manufactured by Nisshin Oillio Group Mineral oil: Moresco White P-70 Triethylhexanoin: TIO, manufactured by Nisshin Oillio Group
[0063] <Evaluation of cosmetics transfer to mask> Each cosmetic product was applied to the skin at a dose of 2.0 mg / cm 2 Water was sprayed onto the area from a spray bottle about 15 cm away for 2 seconds (1 g), and after drying at room temperature for 5 minutes, a black polyester cloth was pressed against the applied area for 3 seconds, the amount of adhesion was visually confirmed, and the transfer of the cosmetic to the mask was evaluated according to the following criteria. (Evaluation Criteria) ⊚: Almost no adhesion to black polyester fabric. ○: A little adhesion to black polyester fabric. △: A lot of it adheres to black polyester fabric.
[0064] <Evaluation of cosmetic product rubbing against mask> Each cosmetic product was applied to the skin at a dose of 2.0 mg / cm 2 Water was sprayed for about 2 seconds (1 g) from a spray bottle about 15 cm away, and after drying for 5 minutes at room temperature, the applied area was rubbed three times with a black polyester cloth, the amount of adhesion was visually confirmed, and the cosmetic product was evaluated for rubbing against the mask according to the following criteria. (Evaluation Criteria) ⊚: Almost no adhesion to black polyester fabric. ○: A little adhesion to black polyester fabric. △: A lot of it adheres to black polyester fabric.
[0065] [Table 2]
[0066] As shown in Table 2, in the cosmetics of Examples 19 to 22, which contained 10 parts by mass or more of the surface-treated powder of the present invention, mask transfer and mask rubbing were suppressed more than in Comparative Example 6. In particular, in Examples 20 to 22, which contained 20 parts by mass or more of the surface-treated powder of the present invention, the effect of preventing mask transfer was even more excellent.
[0067] <Comparison with the sensation when using Fix Mist> The cosmetics of Example 21 and Comparative Example 6 were applied to the skin at a dose of 2.0 mg / cm 2 After application, water was sprayed on Example 21, and a commercially available fix mist was sprayed on Comparative Example 6, and the samples were allowed to dry at room temperature for 5 minutes. Ten panelists were asked to compare the feel of the cosmetic when applied and the feel of the cosmetic film after drying (spreadability when applied, unevenness of application, adhesion, and flexibility after drying) and judged according to the following evaluation criteria. The average scores of the ten panelists are shown in Table 3. (Evaluation Criteria) 5 points: Very superior to Comparative Example 6 4 points: Better than Comparative Example 6 3 points: equivalent to Comparative Example 6 2 points: Inferior to Comparative Example 6 1 point: Very inferior to Comparative Example 6
[0068] [Table 3]
[0069] As shown in Table 3, it was found that the cosmetic of Example 21 had a feel equal to or better than that of the cosmetic of Comparative Example 6, and was also capable of forming a highly flexible cosmetic film that could not be obtained when using a commercially available fix mist.
[0070] The above-disclosed embodiments and examples should be considered as illustrative and not restrictive in all respects. The scope of the present invention is indicated by the claims, not by the above-disclosed embodiments and examples, and includes all modifications and variations within the meaning and scope of the claims.
Claims
1. The base powder is (A) a modified silicone having a carboxyl group; (B) a substance capable of releasing divalent or higher cations; (C) a polymer having a carboxyl group or a sulfonic acid group, which is different from the polymer (A); The surface is treated by The (B) substance capable of releasing divalent or higher cations is one or more oxides, hydroxides, or salts selected from the group consisting of calcium, magnesium, iron, aluminum, and zinc; The surface-treated powder, wherein the polymer (C) having a carboxyl group or a sulfonic acid group and different from the polymer (A) is a carbomer, an acrylates / alkyl acrylate (C10-30) crosspolymer, a xanthan gum, a hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, and / or a sodium acrylate / sodium acryloyldimethyl taurate / dimethylacrylamide crosspolymer.
2. The surface-treated powder described in claim 1, wherein the (A) modified silicone having a carboxyl group is biscarboxydecyl dimethicone and / or carboxydecyl dimethicone.
3. 2. The surface-treated powder according to claim 1, wherein the base powder is at least one selected from the group consisting of talc, titanium oxide, silica, mica, iron oxide, and zinc oxide.
4. A cosmetic comprising 10 parts by mass or more of the surface-treated powder according to any one of claims 1 to 3.
5. A makeup method comprising applying a cosmetic preparation containing the surface-treated powder according to claim 1 to skin to form a cosmetic film, and adhering moisture to the cosmetic film.
Citation Information
Patent Citations
Surface treated zinc oxide powder, and cosmetic containing the same
JP2007277415A
Method for producing cosmetic
JP2009161496A
Organic / inorganic composite particle powder, organic / inorganic composite pigment comprising the organic / inorganic composite particle powder, coating material and resin composition using the organic / inorganic composite pigment, and pigment dispersion and master batch pellet including the organic / inorganic composite pigment
JP2013014767A
Solid powder cosmetic
JP2019006715A
Surface treatment agent, surface-treated powder and cosmetic preparation
WO2009022621A1